Sprog i og uden om SKAM : Autenticitetselement, fællesskabsmarkør og vare - Quist, Pia; Skovse, Astrid Ravn (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2017)
This article argues that language is a key element in the creation of the entire SKAM universe, both inside the series and outside of it in media discourse and fan communities. The use of contemporary Norwegian youth language in the episodes as well as in the characters’ chat and text messages online contribute to the portrayal of a varied gallery of personas and support the experience of authenticity and identification. It is also shown that language works to symbolically construct autonomous youth communities in opposition to adults in the series. Furthermore, the article demonstrates how language is crucial to SKAM’s success in creating transnational fan communities where linguistic elements are used as shareable markers to create a sense of in-groupness among fans. Finally, it is demonstrated that linguistic elements associated with the series have undergone commodification to an extent which exceeds what is normally the case for a public service production.